ALIH KODE DAN CAMPUR KODE PADA INTERAKSI GURU DENGAN SISWA DALAM PEMBELAJARAN BAHASA INDONESIA - Ensri Anjayani; Siti Aisah; Muhammad Zakia Firdaus (Karangan: Jurnal Bidang Kependidikan, Pembelajaran, dan Pengembangan, 2022)
This study aims to describe the form of code switching and code mixing as well as the factors that influence the occurrence of code switching and code mixing events in teacher and student interactions during the teaching and learning process in the classroom. This research is included in qualitative descriptive research. The data in this study were obtained by using the listening method and the following techniques, namely tapping technique, free-involvement-free listening (SBLC) technique, recording technique and note-taking technique. The research data were then analyzed using qualitative descriptive analysis techniques based on sociolinguistic theory. Checking the validity of the data obtained in this study using a triangulation test. The results of the study found that there were 22 utterances of code switching and code mixing found in the teaching and learning process in Indonesian language learning, namely: (1) Internal code switching was 10 utterances and external code switching was 1 utterance. (2) Mixing the internal code of 5 utterances and mixing the external code of 6 utterances. It can be concluded that internal code switching is more dominantly used during teaching and learning interactions in learning Indonesian